Molecularly imprinted polymer for the removal of mercury from petroleum oil - Khairi, Nor Ain Shahera (2016)
Mercury (Hg) is a contaminant is many natural products including hydrocarbon fuels. The presence of mercury can cause problems with downstream processing units as well as safety of workers and environmental issues. Such concern provides incentive to remove the mercury from petroleum oil. Therefore, improvise sorbents is still essential to be further investigates. In recent years, molecularly imprinted polymers (MIPs) have attracted the attention of several researches due to their capability for molecular recognition, easiness of preparation, stability and cost-effective production. By taking advantage of these facts, Hg(II) imprinted polymer and non-imprinted polymer (NIP) were synthesized by bulk polymerization method where cysteine complex (or Lcysteine alone) was polymerized with mercury nitrate (or without it) as a template. Then, methacrylic acid (MAA), 2-hydroxylethyl methacrylate (HEMA), ethylene glycol dimethacrylate (EGDMA) and methanol were added as monomer, co-monomer, cross-linker and solvent respectively. The obtained MIPs were crushed and sieved. The total weight of yield of MIP increased with increasing ratio of monomer, cysteine complex and cross-linker. The temperature used during polymerization was standardized to 70.0°C. The best ratio of monomer to cross-linker is 1:5 while the amount of cysteine complex is 2.0 mmol. FTIR results displayed the presence of S-H in the cysteine complex but there is no peak of S-H observed in MIP-CC spectrum which conclude the interaction between S-H and Hg(II) has occurred. FESEM shows that MIP possess spherical and densely packed particles with rough surface compared with NIP for both cysteine complex (CC) and Lcysteine( LC). Through BET result, the surface area and pore volume of MIP-CC is larger than NIP-CC while for MIP-LC and NIP-LC is vice versa. From TGA result, monomer MAA fully decomposed at lower temperature (197.0°C) compared with MIPCC, NIP-CC, MIP-LC and NIP-LC. The optimum sorption capacity during pH studies was achieved at pH 7 for both MIPCC and MIP-LC. Besides, the sorption of Hg(II) increased by increasing the dosage of MIP. Both MIP-CC and MIP-LC followed Freundlich isotherm with R2=0.9551 and R2 =0.9505 respectively. Meanwhile, the sorption of Hg(II) by MIP is fast within a few second and it is well fitted with pseudo second order reaction. The selectivity result shows that MIP-CC exhibit high selectivity and affinity towards Hg(II) in the presence of competitor ions; Pb(II), Zn(II) and Cd(II) compared with MIP-LC. The reusability of the MIP-CC particles was tested for four times and no significant loss in sorption capacity was observed. From the real samples analysis, the sorption capacities obtained were 93.8% for sludge sample and 29.8% for crude petroleum oil sample with initial Hg(II) concentration of 74.6 μg/L and 1.78μg/L respectively A new type of Hg(II) imprinted polymer as a sorbents for removal of mercury from petroleum oil was successfully synthesized. Prepared MIP-CC showed several characteristic such as high thermal stability, fast sorption kinetic and proper selectivity of Hg(II). Thus, MIP-CC can be potentially used as a sorbents for the removal of mercury petroleum oil.